2005
DOI: 10.1186/bcr1317
|View full text |Cite
|
Sign up to set email alerts
|

Selective estrogen receptor modulators inhibit growth and progression of premalignant lesions in a mouse model of ductal carcinoma in situ

Abstract: Introduction Ductal carcinoma in situ (DCIS) is a noninvasive premalignant lesion and is considered a precursor to invasive carcinoma. DCIS accounts for nearly 20% of newly diagnosed breast cancer, but the lack of experimentally amenable in vivo DCIS models hinders the development of treatment strategies. Here, we demonstrate the utility of a mouse transplantation model of DCIS for chemoprevention studies using selective estrogen receptor modulators (SERMs). This model consists of a set of serially transplante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Overall, the goal of developing a bone specific agent is reasonable, but the key to commercial success will be the prospective demonstration of the prevention of breast and endometrial cancer as beneficial side effects. This remains a possibility based on prevention studies completed in the laboratory [125,126].…”
Section: Metabolic Mimicrymentioning
confidence: 99%
“…Overall, the goal of developing a bone specific agent is reasonable, but the key to commercial success will be the prospective demonstration of the prevention of breast and endometrial cancer as beneficial side effects. This remains a possibility based on prevention studies completed in the laboratory [125,126].…”
Section: Metabolic Mimicrymentioning
confidence: 99%
“…A great majority of DCIS cases express sex-steroid receptors, i.e., estrogen (ER), progesterone (PR), and androgen (AR) receptors (Selim et al 2002, Baqai & Shousha 2003, Moinfar et al 2003, Barnes et al 2005, Rody et al 2005, Kepple et al 2006, which suggest an important role of sex steroids in both DCIS and IDC. Tamoxifen was reported to inhibit the growth of premalignant mammary lesions and the progression to invasive carcinoma in a transplantable mouse model of DCIS (Namba et al 2005). The National Surgical Adjuvant Breast Project (NSABP) P-1 trial demonstrated that tamoxifen significantly reduced the risk of noninvasive breast cancer by 50% (Dunn et al 2005) and results of the NSABP B-24 trial indicated that adjuvant tamoxifen therapy was clinically effective in ER-positive DCIS and reduced the recurrence of non-invasive breast carcinomas by 27% (Cuzick 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a high expression level of ECT2 protein is associated with neoplastic cell transformation, and amplification of the ECT2 gene was found in esophageal squamous cell carcinoma and carcinogeninduced transformed cells (Clemens et al, 2005;Yen et al, 2005). A genetically engineered mouse model of ductal carcinoma in situ, which histologically resembles human breast cancer, showed that upregulated expression of ECT2 occurs during the early stage of malignant transition from normal mammary gland (Namba et al, 2004). Although many studies suggest that deregulated ECT2 expression is involved in cancer progression, it remains unclear how its transcription is regulated, and whether other oncogenes or tumor suppressor genes are related to its regulation.…”
Section: Introductionmentioning
confidence: 99%